Effect of aspirin on cancer incidence and mortality in older adults. - McNeil, John J; Gibbs, Peter; Orchard, Suzanne G; Lockery, Jessica E; Bernstein, Wendy B; Cao, Yin; Ford, Leslie; Haydon, Andrew; Kirpach, Brenda; Macrae, Finlay; McLean, Catriona; Millar, Jeremy; et al. (2020)
BACKGROUND: ASPirin in Reducing Events in the Elderly (ASPREE), a randomized double-blind placebo-controlled trial (RCT) of daily low-dose aspirin (100 mg) in older adults, showed an increase in all-cause mortality, primarily due to cancer. In contrast prior RCTs, mainly involving younger individuals, demonstrated a delayed cancer benefit with aspirin. We now report a detailed analysis of cancer incidence and mortality. METHODS: 19,114 Australian and U.S. community-dwelling participants aged 70+ years (U.S. minorities 65+ years) without cardiovascular disease, dementia or physical disability were randomized and followed for a median of 4.7 years. Fatal and non-fatal cancer events, a prespecified secondary endpoint, were adjudicated based on clinical records. RESULTS: 981 cancer events occurred in the aspirin and 952 in the placebo groups. There was no statistically significant difference between groups for all incident cancers (HR = 1.04, 95% CI = 0.95 to 1.14), hematological cancer (HR = 0.98, 95% CI = 0.73 to 1.30), or all solid cancers (HR = 1.05, 95% CI = 0.95 to 1.15), including by specific tumor type. However, aspirin was associated with an increased risk of incident cancer that had metastasized (HR = 1.19, 95% CI = 1.00 to 1.43) or was stage 4 at diagnosis (HR = 1.22, 95% CI = 1.02 to 1.45), and with higher risk of death for cancers that presented at stages 3 (HR = 2.11, 95% CI = 1.03 to 4.33) or 4 (HR = 1.31, 95% CI = 1.04 to 1.64). CONCLUSIONS: In older adults, aspirin treatment had an adverse effect on later stages of cancer evolution. These findings suggest that in older persons, aspirin may accelerate the progression of cancer and thus, suggest caution with its use in this age group.